2017
DOI: 10.1080/15228053.2017.1313557
|View full text |Cite
|
Sign up to set email alerts
|

Investigating contextual ontologies and document corpus characteristics for information access in engineering settings

Abstract: Knowledge and information resources play a pivotal role in enterprises and are valuable for solution reuse and learning through information access. However, identifying relevant information from a rapidly growing number of unstructured resources is challenging for users. We discuss a personalized information access tool for professional workplaces based on the recommender systems to provide relevant documents for users in specific work contexts based on domain-specific ontologies. Our use case is a multidiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The paper has shown that the manufacturing engineering topic contains many worthy challenges from a search and recommendation perspective. We have examined the use of content-based personalisation [8], user profiles and background knowledge connected to a reference ontology [10], semantic content-based similarity and filesystem features, and developed an overall robust framework for an integrated Information Access system for the KBE domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper has shown that the manufacturing engineering topic contains many worthy challenges from a search and recommendation perspective. We have examined the use of content-based personalisation [8], user profiles and background knowledge connected to a reference ontology [10], semantic content-based similarity and filesystem features, and developed an overall robust framework for an integrated Information Access system for the KBE domain.…”
Section: Discussionmentioning
confidence: 99%
“…4. Documents from multiple sources are ingested and semantically indexed with the help of a domain ontology [10]. The system then is able to provide tailored results to users.…”
Section: Issues Of Personalisation In Professional Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the provision of appropriate information, context-based approaches have been proposed. They help provide knowledge and relevant documents applicable to the engineer's situation [11,36]. Redon et al [11] presented a context-based search platform based on the identification of an engineering context and the subsequent pushing of applicable knowledge to that particular engineer.…”
Section: The Context and Context-based Pui Provision In Product Devel...mentioning
confidence: 99%